Divulging the social sex change mechanism in a unique model system for studying the sexual plasticity of protogynous hermaphrodite fish, three bamboo leaf wrasse (Pseudolabrus sieboldi) - Chakraborty, Tapas; Yamamoto, Yume; Hanai, Shoma; Hirano, Mayumi; Mohapatra, Sipra; Yamaguchi, Akihiko; Takeda, Tatsusuke; Matsuyama, Michiya; Ohta, Kohei (Frontiers in Marine Science, 2022)
The gonadal sexual fate of vertebrates is either defined by genetics or environment, or a combination of both factors. Interestingly, in sequential hermaphroditism, the animal can undergo natural sex changes from female-to-male, male-to-female, and bidirectional way throughout their lives. This change exhibits the process which shifts between oogenesis and spermatogenesis and is regarded as an ideal instance of sexual plasticity. To develop the experimental model for studying the sexual plasticity of protogynous fish, the social conditions that induce sex changes were defined in wrasse, Pseudolabrus sieboldi. When six females were kept together in a tank, the largest female became a male, whereas a similar conversion did not occur when only two females were present in a tank. A semi-gonadectomy analysis developed in the present study verified the direct relationship between gonadal sex and body coloration. In P. sieboldi, the sex change is controlled by the relative body size of an individual within a group, rather than by absolute body size. When 6 females were kept in smaller sized tanks, delayed sex change or unchanged individuals was observed. Overall, more than 90% of the largest females demonstrated sex change after being housed with 5 smaller females in different sizes of tanks ranging from 80 to 500L. Furthermore, the experiment using a transparent barrier suggested that visual stimuli are one of the major cues to initiate sex change. Our findings on the laboratory conditions leading to the initiation of sex change in wrasse suggest the usefulness of this species as a model organism for comparative studies in molecular, cellular, and physiological mechanisms of sexual plasticity, as well as on social and reproductive behaviors.